Real‐time assessment of individual optimal CT perfusion acquisition time in patients with ischemic stroke. Issue 4 (17th May 2022) - Filice, Silvano; Pavarani, Antonio; Cerasti, Davide
Abstract: Background and Purpose: This study aims to investigate the feasibility of a "real‐time" estimate of the optimal CT perfusion (CTP) acquisition time ( T op ) in ischemic stroke patients. Methods: The arterial input function, the venous output function (VOF), and the time‐attenuation curves of ischemic core and ischemic penumbra of 51 patients with acute ischemic stroke in anterior circulation were obtained. The curves were analyzed to determine for each patient the T op value; additionally, several time parameters were derived from each waveform. The relationship between each of these parameters and T op was investigated. Results: We found a strong linear correlation between each time parameter derived from VOF curve and T op, suggesting that the VOF waveform is rescaled from patient to patient without significant change in shape. Conclusions: The linear correlation between T op and the VOF time to peak is well suited to implement a new technique to automatically customize the patient's CTP acquisition time. The method does not require an additional dose of contrast medium and does not increase the overall study time, so its use would be desirable to decrease the average radiation dose.